Exploration of the quantitative-effectiveness association between acupuncture temporal parameters and chemotherapy-induced peripheral neuropathy in cancer patients: a dose-response meta-analysis of randomized controlled trials - Tian, Hao; Luo, Qin; Huang, Liuyang; Chen, Guang; Sun, Mingsheng; Liang, Fanrong (Frontiers in Oncology, 2025)
BackgroundChemotherapy-induced peripheral neuropathy (CIPN) is one of the commonly reported symptoms impacting cancer survivors. This study evaluated and compared the effectiveness of acupuncture treatments for CIPN.MethodsWe searched six databases from their inception to August 2024 to identify eligible randomized controlled trials (RCTs). Primary outcome were pain scores. Secondary outcomes were quality of life including FACT/GOG-Ntx and EORTC QLQ-C30. The robust error meta-regression (REMR) method was used to evaluate the dose-response relationship across treatment parameters, including number of sessions, frequency, and duration.ResultsIn total, 11 RCTs featuring 740 participants were included. The meta-analysis demonstrated that the primary analysis achieved a significant reduction in pain scores, with a standardized mean difference of [SMD= -1.23, 95% CI = (-2.22, -0.24); P < 0.01; I² = 95%], improvement quality of life including FACT/GOG-Ntx [SMD = 0.95, 95% CI = (0.02, 1.88); P < 0.01; I² = 93%] and EORTC QLQ-C30 [SMD = 0.36, 95% CI = (0.03, 0.68); P = 0.14; I² = 46%]. The nonlinear dose-response analysis suggests that pain improvement achieves the MCID at 16 treatment sessions, over 8 weeks, with a frequency of twice per week. Furthermore, analysis of the treatment duration chart shows that acupuncture maintains therapeutic effects during the follow-up period. Sensitivity analysis confirmed the robustness of these findings.ConclusionAcupuncture demonstrates significant potential in managing CIPN, particularly through individualized treatment regimens. The identified time-dose-response relationship suggests that tailoring acupuncture frequency and duration can to optimize pain relief in CIPN patients. Future high-quality studies and large-scale multicenter clinical trials are needed to validate these findings.